Influence of a 12-year supervised physical activity program for the elderly</d> - José Rodrigo Pauli; Luciana Santos Souza; Anderson Saranz Zago; Sebastião Gobbi (Universidade Federal de Santa Catarina, 2009)
Aging is an inevitable process and is associated with declining physiological and functional capacity in humans. The objective of this study was to determine the effects of a 12-yearsupervised physical training program on functional fitness in the elderly. Ten women (mean age: 65 years) participated in the study. The subjects were divided into two groups: a) a trained group consisting of women who had been attending a supervised program including different types of physical activities of moderate intensity over the last 12 years; b) an untrained group consisting of women who were not engaged in any supervised physical activity program over the last 12years. Functional fitness was assessed using the AAHPERD field-test battery which comprises five single motor tests: coordination, flexibility, strength endurance, agility and dynamic balance, and overall aerobic endurance. The results showed a better performance of elderly women whoparticipated in a physical activity program over the last 12 years. Thus, whereas elderly women who perform regular physical activities in a supervised program tend to show improvement of all functional fitness components even after a period of 12 years, a tendency towards a reduction in most of these components is observed in their non-active peers. These findings seem to predict an increasing gap in functional fitness between these two groups as they grow older, with opposite effects on the quality of life of these subjects.